Welcome to the Final Issue of the College’s Asia Pacific Journal of Health Management for 2024 - Neale Fong (Asia Pacific Journal of Health Management)
I want to take this opportunity to thank all the volunteers who support the Australasian College of Health Service Management. It is the work of dedicated volunteer College members, alongside our hardworking staff, which ensure we can continue to deliver the multitude of free and other programs that support the development of health managers and leaders, wherever our members are.